In vivo regulation of the monocyte phenotype by Mycobacterium marinum and the ESX-1 type VII secretion system - Kristina Munke; Line Wulff; Julia Lienard; Fredric Carlsson; William W. Agace (Scientific Reports)
Abstract Pathogenic mycobacteria require the conserved ESX-1 type VII secretion system to cause disease. In a murine Mycobacterium marinum infection model we previously demonstrated that infiltrating monocytes and neutrophils represent the major bacteria-harbouring cell populations in infected tissue. In the current study we use this model, in combination with scRNA sequencing, to assess the impact of M. marinum infection on the transcriptional profile of infiltrating Ly6C⁺MHCII⁺ monocytes in vivo. Our findings demonstrate that infection of infiltrating monocytes with M. marinum alters their cytokine expression profile, induces glycolytic metabolism, hypoxia-mediated signaling, nitric oxide synthesis, tissue remodeling, and suppresses responsiveness to IFNγ. We further show that the transcriptional response of bystander monocytes is influenced by ESX-1-dependent mechanisms, including a reduced responsiveness to IFNγ. These findings suggest that mycobacterial infection has pleiotropic effects on monocyte phenotype, with potential implications in bacterial growth restriction and granuloma formation.